Reservoir Simulator For Improved Recovery Of Coalbed Methane (Icbm) Part I: Model Formulation And Comparison - Ego Syahrial (Scientific Contributions Oil and Gas, 2009)
Sequestration of CO2 in deep unmined coal seams is currently under development for improved recovery of coalbed methane (ICBM) as well as permanent storage of CO2. Recent studies have shown that CO2 displaces methane by adsorbing more readily onto the coal matrix compared to other greenhouse gases, and could therefore contribute towards reducing global warming. In order to carry out a more accurate assessment of the potential of ICBM and CO2 sequestration, field based numerical simulations are required. Existing simulators for primary CBM (coalbed methane) recovery cannot be applied since the process of CO2 injection in partially desorbed coalbeds is highly complex and not fully understood. The principal challenges encountered in numerical modelling of ICBM/CO2 sequestration processes which need to be solved include: (1) two-phase flow, (2) multiple gas components, (3) impact of coal matrix swelling and shrinkage on permeability, and (4) mixed gas sorption. The objective of this part I of this two-part paper series is to develop a two-phase, multi-component CH4-CO2 simulator for use in the assessment of CO2-ICBM recovery and CO2 sequestration potential of coal seams. The developed formulation was tested and compared to model the improved coalbed methane (ICBM) recovery with pure CO2 injection using a published data.